Critical Role of Oxidatively Damaged DNA in Selective Noradrenergic Vulnerability. (1st December 2019) - Zhan, Yanqiang; Raza, Muhammad U.; Yuan, Lian; Zhu, Meng-Yang
Graphical abstract: Highlights: Effects of H2 O2 on cell viability and DNA damage were compared in cultured cells. M17 cells and LC cultures showed more cell death, DNA damage and higher ROS. M17 cells showed an increased protein levels of NET, Cav 1.2 and Cav 1.3. M17 cells showed a reduced expression of copper transporter and OGG1. Noradrenergic cells are more vulnerable to H2 O2 than dopaminergic cells. Abstract: An important pathology in Parkinson's disease (PD) is the earlier and more severe degeneration of noradrenergic neurons in the locus coeruleus (LC) than dopaminergic neurons in the substantia nigra. However, the basis of such selective vulnerability to insults remains obscure. Using noradrenergic and dopaminergic cell lines, as well as primary neuronal cultures from rat LC and ventral mesencephalon (VM), the present study compared oxidative DNA damage response markers after exposure of these cells to hydrogen peroxide (H2 O2 ). The results showed that H2 O2 treatment resulted in more severe cell death in noradrenergic cell lines SK-N-BE(2)-M17 and PC12 than dopaminergic MN9D cells. Furthermore, there were higher levels of oxidative DNA damage response markers in noradrenergic cells and primary neuronal cultures from the LC than dopaminergic cells and primary cultures from the VM. It included increased tail moments and tail lengths in Comet assay, and increased protein levels of phosphor-p53 and γ-H2AX after treatments with H2 O2 . Consistent with these measurements, exposure of SK-N-BE(2)-M17 cells to H2 O2 resulted in higher levels of reactive oxygen species (ROS). Further experiments showed that exposure of SK-N-BE(2)-M17 cells to H2 O2 caused an increased level of noradrenergic transporter, reduced protein levels of copper transporter (Ctr1) and 8-oxoGua DNA glycosylase, as well as amplified levels of Cav 1.2 and Cav 1.3 expression. Taken together, these experiments indicated that noradrenergic neuronal cells seem to be more vulnerable to oxidative damage than dopaminergic neurons, which may be related to the intrinsic characteristics of noradrenergic neuronal cells.